Occupational stress, coping strategies, and associated factors among primary healthcare workers in Vietnam - Han Thi Ngoc Nguyen; Phi Hoang Nguyen; Han Thi Ngoc Nong; Ly Trieu Vo; Dung Dang Nguyen; Nhi Thi Bui; Yen Nhi Thi Nguyen; Giao Huynh (PLoS ONE, 2026)
Background Occupational stress is a growing concern among healthcare workers (HCWs), particularly in primary care settings where responsibilities are multifaceted and resources are limited. Objective This study aimed to determine the proportion of perceived stress levels, identify the coping strategies employed, and explore sociodemographic, familial, and occupational factors associated with stress among HCWs in a district-level health system in Ho Chi Minh City, Vietnam. Methods A cross-sectional study was conducted from 19 February 2025–31 March 2025 involving 212 HCWs selected through total population sampling. Data were collected using a structured self-administered questionnaire comprising the 10-item Perceived Stress Scale (PSS-10) and the Brief COPE inventory. Descriptive statistics summarized participant characteristics and stress levels. Comparisons were performed using independent t-tests and one-way ANOVA, while Spearman’s rank correlation explored associations between continuous variables. Variables with p < 0.20 in univariate analysis were included in a multivariate linear regression model with backward elimination to identify independent predictors of stress. Multicollinearity was assessed using the Variance Inflation Factor (VIF). Results The mean PSS-10 score was 16.7 ± 2.3, with 93.4% of participants experiencing moderate stress and 6.6% low stress. The most frequently endorsed coping strategies were denial (5.8 ± 1.2), behavioral disengagement (5.4 ± 1.4), and substance use (5.0 ± 1.1). Multivariate analysis revealed that younger age, having chronic diseases, and being a physician were independently associated with higher perceived stress. Conclusion The study reveals a high prevalence of moderate stress among HCWs in primary care, with frequent use of ineffective coping strategies. Interventions should be tailored to promote effective coping, reduce occupational burdens, and provide targeted support to vulnerable subgroups.